Hakikat Pendekatan dan Metode Dalam Pembelajaran Bahasa - Bidin, S.Ag., M.Pd. (AL-IBNOR, 2023)
So far, there has been an impression of mixing understanding between approaches, methods, and techniques in learning. In the lesson plan, it is often said that lectures, discussions, assignments, and questions and answers are a method. While others refer to learning techniques. Some say "communicative" it's an approach. While others say methods. As a result, the misinterpretation of the term is brought by the teacher in the process of language learning. Indeed, basically the understanding between approaches, methods, and learning techniques is different. But that distinction is sometimes not very obvious if we are less careful about applying these terms. Not only on the issue of perception, at the production stage there is often an overlap in the use of these terms.